Colon perforation after esophagogastroduodenoscopy in an asymptomatic diverticulitis patient. Issue 1 (22nd April 2015) - Huang, Li‐Wen; Lin, Chun‐Che; Chen, Tan‐Hsia; Lee, Hsiang‐Lin; Tsia, Chung‐Hung
Summary: Esophagogastroduodenoscopy (EGD) is regarded as a relatively safe procedure; however, it carries a very low incidence of severe adverse events. Perforation is a rare complication of EGD, and it may further lead to pneumoperitoneum or pneumoretroperitoneum. The occurrence of large bowel perforation after EGD is extremely rare, and it has never been reported in the international literature. Herein, we present a case of concurrence of pneumoperitoneum and pneumoretroperitoneum as a result of sigmoid perforation after EGD. In our case, the probable mechanism of the perforation may have stemmed from the excessive inflation of air that passed through the gastrointestinal tract to the sigmoid colon, causing the increased intraluminal pressure, and then prompting a healed asymptomatic diverticulitis leak again.